Persistence of secukinumab in patients with psoriasis, psoriatic arthritis, and ankylosing spondylitis - Elena Conesa-Nicolás; María Henar García-Lagunar; Sara Núñez-Bracamonte; María Sergia García-Simón; María Carmen Mira-Sirvent (Farmacia Hospitalaria, 2021)
Objective: To determine persistence of treatment with secukinumab across its different indications. Method: This is a retrospective descriptive observational study including adult patients treated with secukinumab in its different indications from the drug’s introduction in November 2015 to October 2019. The variables included were sex; age; diagnosis; initiation date; line of treatment; number of patients who discontinued treatment and reason for discontinuation; overall persistence at 12 months; distribution of patients; and persistence according to indication, line of treatment and reason for suspension. Results: One-hundred forty-three patients were started on secukinumab, but only patients who had been in treatment at least 12 months before the end of the study were included. Mean patient age was 49.8 years (±12.6); 52.9% were men. Fifty-six patients (53.8%) had discontinued treatment by the end of the study, with a mean duration of treatment of 12.7 months (±10.2). The other patients (n = 48) continued with their therapy. Mean duration of treatment in these patients was 25.7 months (±9.9). Overall persistence at 12 months was 10.0 months (±3.3) with a discontinuation rate at 12 months of 31.7%. Persistence at 12 months was 10.7 months (±2.9) for patients with psoriasis, 9.7 months (±3.4) for patients with psoriatic arthritis, and 8.8 months (±3.8) for those with ankylosing spondylitis. Of the 48 patients who continued with their treatment after completion of the study, 22 (45.8%) received the drug as first-line treatment. Of the 56 discontinuations, 15 (26.8%) were due to primary failure (persistence: 3.8 months [±1.1]) and 27 (48.2%) were due to secondary failure (persistence: 18.6 months [±9.6]). Persistence in patients who continued treatment was higher in psoriasis (28.8 months [±10.3]). In those who discontinued due to secondary failure it was higher in the group with ankylosing spondylitis (28.0 months [±4.2]). Persistence among patients on first-line secukinumab was higher than for other patients: 21.2 months (±7.2) if they stayed on treatment, 3.5 months (±0.5) if they presented with primary treatment failure, and 8.3 months (±2.5) in those with secondary treatment failure. Conclusions: Our data show slightly higher persistence levels in patients with psoriasis and lower discontinuation rates in those without previous exposure to biological therapy. Long-term studies are needed to confirm these findings and to gain a better understanding of the factors that can influence persistence of secukinumab.